Penyuluhan Jenis Terapi Komplementer untuk Menjaga Kesehatan Mental Pada Remaja di UPT SMAN 13 Bone - St.Malka; Mutmainnah Mutmainnah (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Free association among adolescents is a social problem that is increasingly worrying, especially in the current era of globalization. Adolescents’ lack of understanding regarding behavioral boundaries in social interactions can have various negative impacts, both physically, psychologically, and socially. To address this, this community service activity was conducted with the aim of providing education about the dangers of free association to students of MA Mathla’ul Anwar Pandeglang. A total of 25 students participated in this activity. The media used was a snakes and ladders game that had been educationally modified to suit the material presented. The implementation method included interactive lectures, educational games, group discussions, and learning evaluations through pre- and post-tests. The results of the activity showed a 34% increase in students’ understanding of the dangers of free association after participating in the entire series of activities. In addition, the snakes and ladders game media proved effective as a fun learning tool and was able to increase active student participation. This game also helped students more easily understand and remember the material presented. With this creative and participatory approach, it is hoped that education about healthy associations and adolescent character can be better accepted and implemented in everyday life. This activity is expected to become an alternative model for character education in schools and can be implemented sustainably in various educational institutions.